2008
DOI: 10.1111/j.1467-8624.2008.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

In Defense of Qualitative Changes in Development

Abstract: The balance between the preservation of early cognitive functions and serious transformations on these functions shifts across time. Piaget's writings, which favored transformations, are being replaced by writings that emphasize continuities between select cognitive functions of infants and older children. The claim that young infants possess elements present in the older child's concepts of number, physical impossibility, and object permanence is vulnerable to criticism because the inferences are based primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 148 publications
2
54
0
4
Order By: Relevance
“…A unifying aim for developmental psychology is to understand the processes of change in human behavior Kagan, 2008;Muller & Giesbrecht, 2008). Theories of development are often contrasted in terms of their accounts of change, in particular whether processes of change are qualitative or quantitative, and continuous or discontinuous.…”
mentioning
confidence: 99%
“…A unifying aim for developmental psychology is to understand the processes of change in human behavior Kagan, 2008;Muller & Giesbrecht, 2008). Theories of development are often contrasted in terms of their accounts of change, in particular whether processes of change are qualitative or quantitative, and continuous or discontinuous.…”
mentioning
confidence: 99%
“…Evidence has shown that the "developmental processes are highly nonlinear, heterogeneous, and dependent on a wide range of factors" (Rose & Fischer, 2009, p. 417). Other characteristics of the developmental processes are the multi-causality as a relationship between diverse factors, and the discontinuity, or abrupt changes in behavior (Kagan, 2008, Spencer & Perone, 2008PucheNavarro, Combariza, Ossa, 2012). These characteristics of developmental processes required to leave behind the notion of "stages" as fixed upward sequences.…”
Section: A Emergência Do Planejamento Cognitivo a Curto Prazo: Desempmentioning
confidence: 99%
“…Despite the many strengths of this article, and although various research findings have also been used in the field to argue for or against rich and lean interpretations of the development of various cognitive and social cognitive capacities [e.g., Aslin & Fiser;2005;Baillargeon, Scott, & He, 2010;Bremner & Mareschal, 2004;Kagan, 2008;Munakata, Bauer, Stackhouse, Landgraf, & Huddleston, 2002;Rakison, 2007;Tomasello, Carpenter, & Liszkowski, 2007], the elephant on the table in this sort of work is that the entire reason for the rich-lean dichotomy is that identical forms of behavior can be given a rich or a lean interpretation [Racine, 2012;Rakoczy, 2012]. Although new empirical studies and empirical findings in general can be used to render richer or leaner views less plausible, when a research area has reached the point of a protracted rich-lean debate, in my view the controversy is usually turning on issues that cannot be entirely resolved empirically.…”
Section: Racinementioning
confidence: 99%